Impact of floor management practices on the growth of groundcover species and soil properties in an apple orchard in northern China. Issue 4 (4th July 2018) - Ping, X. Y.; Wang, T. M.; Yao, C. Y.; Lu, X. S.
Abstract: Tillage and groundcover are the two mainly used management practices in orchard. Only small portion of orchard has been treated with groundcover in China, which would restrict our understanding of the scientific management of apple orchard. This study aimed to investigate the impact of different groundcover treatments on the plant growth of groundcover species and soil properties in an apple orchard near Beijing, northern China. Six commonly used groundcover species were chosen to grow underground. Our results showed that groundcover species had significant greater maximum photosynthesis rate ( P max ) than weeds in control plots. Meanwhile, groundcover treatments could largely improve the microclimate of orchard compared with tillage treatment. Among all the groundcover species, alfalfa was proven to be the most appropriate species grown underground in apple orchard for its high P max and high above-ground biomass. Groundcover treatments had little impact on soil bulk density, soil porosity and surface soil organic carbon (SOC) content. However, significantly greater deep soil organic carbon contents were found in two grass species, and significantly higher soil available nitrogen (N) contents were found in two leguminous species respectively. Our results indicated that groundcover treatment would be a sustainable management practice for apple orchard in northern China.